Why Are Healthcare Workers and Hospitals Required to Implement Infection Control Policies - Sawsan Abdullah Ali Alamri; Areej Ibraheem Alyami; Othman Saleh Zahrani; Rashed Khalid M Alanazi; Abdulrahman Mohammed A Majrashi; Ali Ahmed Mohamed Alshajeri; Ammar Arab; Dr. Abdullah Ali Aldamkh (International Journal of Medical Toxicology and Legal Medicine, 2025)
Infection control is a fundamental component of quality healthcare delivery, playing a pivotal role in safeguarding patients, healthcare workers, and the broader community. This paper investigates the rationale behind the mandatory implementation of infection control policies in healthcare institutions. It delves into eight critical areas: the prevention of healthcare-associated infections (HAIs), the protection of healthcare personnel, the assurance of patient safety, compliance with legal and regulatory frameworks, effective outbreak and pandemic response, public trust and institutional credibility, economic efficiency, and the promotion of antimicrobial stewardship. Through a comprehensive review of current guidelines, evidence-based practices, and global health standards, this paper underscores how infection control serves as a cornerstone of safe, effective, and sustainable healthcare systems. By enforcing robust infection prevention protocols, healthcare facilities can significantly mitigate risks, enhance outcomes, and contribute to global efforts against infectious disease threats.